DETERMINATION OF PESTICIDE RESIDUES IN MUSCLE AND ORGANS OF COW, CAMEL AND GOAT IN BIRNIN KEBBI, KEBBI STATE, NIGERIA - Osesua, Anthony; Omoniyi, Fasiku (International Journal of Environmental Sciences, 2022)
Pesticide residues in muscle and organs of farm animals (cow, camel and goat) were assessed. Samples of muscle (meat), liver, kidney and heart were collected from central abattoirs in the four emirate councils of Kebbi State in order to determine their level of contamination. Residues were extracted from the samples using standard operating procedures and analysed with GC-MS (Intuvo 9000 model) coupled with ECD. Total pesticide residues in the samples ranged from 0.113 to 2.532µg/Kg (muscle), 0.095 to 2.341µg/Kg (liver), 0.047 to 0.931µg/Kg (kidney and 0.026 to 0.361µg/Kg (heart). Pesticide residues concentrations were in the order; muscle > liver > kidney > heart. Analysis of the results obtained also shown that 12.150% of samples from Yauri emirate were contaminated with pesticide residues, 11.249% were contaminated from Argungu, 7.834% from Zuru and 5.784% from B/Kebbi. Samples of muscle and organs from cow accumulated 47.04% of the detected pesticide residues, Camel accumulated 44.48% of the detected residues and goat muscles and organs accumulated 8.48% of the detected pesticide residues. The concentrations of all the assessed pesticides observed in the muscle and organs were however lower than the recommended maximum residual limits (MRLs).